The Effect of Pandemic News on Stock Market Returns During the Covid-19 Crash: Evidence from International Markets - (:unkn) unknown (ISTANBUL UNIV, FAC COMMUNICATION, 2021)
This study investigates the effect of pandemic-related news on stock market returns in international markets using the quantile regression method. The media hype index, fake news index, country sentiment index, infodemic index, and media coverage index provided by the RavenPack data platform are used for the analysis. In this research, 2,996 observations from 80 countries, consisting of daily data from January 22, 2020, to April 17, 2020, were used. The results show that the impact of Covid-19-related news on market returns varies among the quantiles of the stock market; in other words, there is an asymmetric dependency between the news and financial markets. With the increase in coverage about the pandemic in the media, the negative impact on market returns exhibits a decreasing trend from low quantiles to high quantiles. More intense use of effective communication channels is required to alleviate the financial crash caused by Covid-19. To capture the effect of the news on financial markets, this analysis also categorized countries according to the Morgan Stanley Classification Index (MSCI, n.d.), such as by developed, emerging, standalone, and frontier markets and by geographical location, including Europe, Africa, North and South America, Asia, and the Middle East. The results are consistent with the previous findings and the dependency between the news and financial markets remains asymmetric.
Keywords: Covid-19; financial markets media hype index; country sentiment index; media coverage index; quantile regression; SENTIMENT; MEDIA; UNCERTAINTY